THE EFFECT OF INCENTIVES, JOB COMMITMENT, WORK DISCIPLINE, AND WORK MOTIVATION ON WORK ACHIEVEMENT IN THE FIELD OF HEALTH SERVICES AND SDK OF THE HEALTH OFFICE OF POPULATION CONTROL AND FAMILY PLANNING OF LINGGA DISTRICT - Jufri, Jufri; Settambul, Uking Kesid; Anggarsari, Nuzuliana; Sabri, Sabri; Sumardin, Sumardin (Yayasan Education and Social Center, 2024)
This study aims to identify the effect of incentives and job commitment on employee work performance in the Health Service and SDK Division of the Health, Population Control, and Family Planning Office of Lingga Regency. Primary data, which was obtained through questionnaires and direct interviews with 39 employees, was the type of data utilized. Various methods, such as observation, interviews, and the distribution of questionnaires, are employed to collect data. Data analysis was carried out using validity and reliability tests and multiple linear regression to evaluate the effect of independent variables on dependent variables. The analysis results show that incentives significantly affect work performance, with a determination coefficient of 66.1%. In comparison, task commitment has a significant effect with a determination coefficient of 53.7%. The t-test and F-test support the hypothesis that both independent variables significantly affect work performance. These findings provide important insights for management in designing incentive strategies and increasing task commitment to improve employee performance in the health sector. This study is expected to be a reference for further research on factors influencing work performance in public service organizations